A Detailed Study of a Resonant-Assisted Segmented Cladding Fiber for Large Mode Area Applications - Minmin Xue; Hao Qin; Suwen Li; Yuqi Hao; Libo Yuan (Photonics)
In this work, we have proposed and optimized a large mode area segmented cladding fiber (SCF) with an unconventional low-index segment cladding. The low-refractive-index cladding proposed in this paper consists of three parts. There three geometric parameters chosen as design variables were the length and width of the first part and the leg length of the isosceles trapezoid in the second part. To investigate the properties of the proposed SCF, numerical modeling based on the finite element method (FEM) was performed. A high leakage loss ratio (>9000) between the high-order modes (HOMs) and the fundamental mode was achieved at a wavelength of 1310 nm, which is significantly higher than that of conventional SCFs. Additionally, the mode area of the proposed fiber reaches 890 µm2 at a core radius of 20 µm. The bending effects on the SCF were also studied. When the bending radius is greater than 0.3 m, the mode area greater than 880 µm2 and remains stable, and the leakage loss of the least high-order mode (LP11h) exceeds 30 dB/m. The new fiber design demonstrates significant potential for high-power fiber lasers